"Ticos auténticos... que no hablan español" Ideologías sobre las lenguas minoritarias y la diversidad lingüística de Costa Rica - Sánchez Avendaño, Carlos (2014)
This article analyzes some linguistic ideologies in written sources (academic discourse, press, school textbooks and journey chronicles) concerning the Costa Rican indigenous languages, the Limon creole English and the Costa Rican sign language. Basically, the following ideological axis are commented: the linguistic superiority and the types of languages, the relation between language and cognitive-intellectual capacities, the link between linguistic variation and writing, and the relationship between language and identity.